2014
DOI: 10.3923/pjbs.2015.46.49
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Cytotoxicity Studies of Aqueous and Ethanolic Leaf Extracts of Chromolaena odorata

Abstract: Chromolaena odorata, a commonly used traditional remedy for different ailments, believed to be quite safe in terms of toxicity was evaluated for acute toxicity and cytotoxic potentials. Acute toxicity was done on albino Wistar rats using the Lorke method while brine shrimps were used to test for cytotoxicity. The results showed that the estimated LD50 for the aqueous and ethanolic extracts was 2154 and > 5000 mg kg(-1) body weight, respectively. Cytotoxicity to brine shrimps showed LC50 values of 324 and 392 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…High ash content of these plants is actually a measure of the mineral richness 4% crude fiber and 16.2% crude protein. The reported data was in accordance with the present research findings[30]. The proximate analysis of the C. sativa plant parts separately and reported 6.87 % moisture, 11.18% ash, 23.78% crude proteins and 18.95% crude fiber in the leaf.The proximate analysis of four medicinal plants[32] including M. longifolia and reported the highest crude protein value of 7.49% and 2.34% of crude fat in M. longifolia[22] which were in complete accordance with present data while moisture content was lower than present results.…”
supporting
confidence: 92%
“…High ash content of these plants is actually a measure of the mineral richness 4% crude fiber and 16.2% crude protein. The reported data was in accordance with the present research findings[30]. The proximate analysis of the C. sativa plant parts separately and reported 6.87 % moisture, 11.18% ash, 23.78% crude proteins and 18.95% crude fiber in the leaf.The proximate analysis of four medicinal plants[32] including M. longifolia and reported the highest crude protein value of 7.49% and 2.34% of crude fat in M. longifolia[22] which were in complete accordance with present data while moisture content was lower than present results.…”
supporting
confidence: 92%
“…Asomugha et al, 32 extracted C. odorata leaves from Nigeria with water and ethanol (1:10 w/v) for 24 h. The cytotoxicity to brine shrimp showed LC 50 values of 324 and 392 ppm for aqueous and ethanol extracts, respectively. Olowa and Nuneza 33 extracted 20 g of C. odorata leaves from the Philippines with 250 ml of ethanol for 48 h. The brine shrimp lethality concentration LC 50 value was 10 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in body weight of the test groups of the rats after administration of Chromolaena odorata (linn) fresh leaf extract (Table 4), is justified by Kewuchi et al, 36 who reported a reduction of weight gain produced by the administration of the plant extract. The plant has been reported to be rich in phytochemicals such as flavonoids, terpenes and tannins; and essential oils 16,37,38 . The phytochemical contents of this plant could be responsible for the weight loss in the test animals in this study.…”
Section: Resultsmentioning
confidence: 99%